Characteristic alterations of gut microbiota and metabolites in patients with perianal abscess: a multi-omics analysis - Ma, Huangfu; Fang, Jingjing; Li, Mengjie; Qin, Yige; Wang, Yanmei; Kang, Seong-Gook; Huang, Kunlun; Tong, Tao (Frontiers in Microbiology, 2025)
Background/objectivesVarious studies have highlighted the important associations between perianal abscess (PA) and gut microbiota and related metabolites. Nevertheless, the establishment of causal relationships between these associations remains to be determined. This study aimed to provide direct evidence and a comprehensive understanding of gut microbiota disturbance in children with PA through combined 16S rRNA sequencing and untargeted metabolomic analysis.MethodsThirty three children with PA and 16 healthy controls (HC) were continuously enrolled, and the demographic and clinical characteristics of the subjects were collected. First, 16S rRNA sequencing was used to evaluate differences in the gut microbiota between children with PA and the HC group, and 10 children with PA and 10 children in the HC group were randomly selected for non-targeted metabolomic analysis.ResultsThere were significant differences in the gut microbiota diversity and composition between children with PA and HC. Comprehensive analyses revealed an elevation of the genus Enterococcus and a depletion of the phylum Firmicutes as well as Eubacterium_hallii_group, Faecalibacterium, Blautia, and Fusicatenibacter at the genus level in children with PA. Non-targeted metabolomics detected 1168 different metabolites between children with PA and HC. Functional analysis of the gut microbiota and KEGG pathway enrichment analysis of differential metabolites between the PA and HC groups corroborated that the pathways of phenylalanine, tyrosine and tryptophan biosynthesis, valine, leucine and isoleucine biosynthesis, and pantothenate and CoA biosynthesis were down-regulated in children with PA, while the pathways of ubiquinone and other terpenoid-quinone biosynthesis, tyrosine metabolism, and tryptophan metabolism were up-regulated in children with PA. The correlation analysis highlighted meaningful associations between the altered microbiota and specific metabolic profiles, further underscoring the complex interplay between microbial composition and metabolic function in the pathogenesis of PA in children.ConclusionsThis study provides new evidence of the pathogenesis of PA. There are significant differences in the gut microbiota, metabolites, and metabolic pathways between HC and children with PA, and the differences in metabolites are related to specific changes in bacterial abundance. These findings provide a foundation for future studies aimed at exploring targeted microbiome-based therapeutic strategies for managing PA in pediatric populations.